Odd Harmonious Labeling of the Zinnia Flower Graphs - Fery Firmansah; Tasari Tasari; Muhammad Ridlo Yuwono (Sam Ratulangi University, 2023)
An odd harmonious graph is a graph that satisfies the odd harmonious labeling properties. In this study, a new graph class construction is presented, namely zinnia flower graphs and variations of the zinnia flower graphs. The research method used is qualitative and includes several phases, namely data collection, data processing and analysis, and verification of the results. The purpose of this research is to find a new class of graphs that is a family of odd harmonious graphs. We will prove that prove that the zinnia flower graph and its variations satisfy odd harmonious labeling properties. The result of this research is that the zinnia flower graph and its variations are odd harmonious graphs. Keywords: Flower graph; odd harmonious graph; odd harmonious labelling; zinnia flower graph Pelabelan Harmonis Ganjil dari Graf Bunga Zinnia ABSTRAK Graf yang memiliki sifat pelabelan harmonis ganjil adalah graf harmonis ganjil. Pada penelitian ini akan didapatkan konstruksi graf bunga zinnia dan variasi graf bunga zinnia. Metode penelitian yang digunakan adalah penelitian kualitatif yang terdiri beberapa tahapan yaitu pengumpulan data, pengolahan dan analisis data, serta verifikasi hasil. Tujuan penelitian ini adalah menemukan kelas graf baru yang merupakan keluarga dari graf harmonis ganjil. Hasil penelitian ini diperoleh bahwa graf bunga zinnia dan variasi graf bunga zinnia merupakan graf harmonis ganjil. Kata kunci: Graf bunga; graf bunga zinnia; graf harmonis ganjil; pelabelan harmonis ganjil